Evaluation of financial monitoring systems effectiveness in its relationship to the country’s security indicators - Ksendzuk, Valentyna; HRYTSYSHEN, DYMYTRII; SERGIIENKO, LARYSA; HRABCHUK, IRYNA; ZAKHAROV , DMYTRO (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The motivation for this research work is its potential to identify critical issues with far-reaching implications for economic security, governance and development, and to contribute to more informed decision-making in the area of countering the financing of terrorism. Aim: The purpose of this research paper is to analyse the impact of the FATF (Financial Action Task Force) standards on crime and anti-corruption efforts and the effective implementation of the legal framework in countries. Results: The article examines the relationship between crime, corruption, terrorism and FATF standards in 54 countries. Based on the regression analysis, the influence of crime, terrorism and perception of corruption on the effectiveness and compliance with FATF standards is investigated. The specific coefficients show that the perception of terrorism and corruption have a statistically significant negative and positive impact on the dependent variable, respectively, while the impact of the crime index is not statistically significant. By examining the impact of crime rates and anti-corruption efforts on FATF standards and the effective implementation of legal frameworks in countries, the study aims to provide information that can inform decision-making. Understanding how these factors interact can help to improve anti-money laundering and counter-terrorist financing strategies at both the national and international levels, including the improvement of financial monitoring systems. Understanding the relationship between crime, corruption and terrorism can have practical implications for various stakeholders, including law enforcement, government officials and international organisations. The findings are important for the implementation of effective measures to combat money laundering and terrorist financing, improve governance, security and overall socio-economic stability.